A systematic review of the impact of COVID-19 on the game addiction of children and adolescents - Han, Tae sun; Cho, Heejun; Sung, Dajung; Park, Min-Hyeon (Frontiers in Psychiatry, 2022)
Background: During the COVID-19 pandemic, it is reported that children and adolescents who are socially isolated experience high levels of stress and various mental health problems. At present, little research has been done to collect previous studies that focused on game addiction in children and adolescents during the COVID-19 pandemic. In this research, we aimed to investigate the prevalence of gaming disorder during COVID-19 in children and adolescents and the various factors experienced by children and adolescents that affected gaming disorder. Methods: We searched PubMed, Embase, PsycINFO, and Cochrane on 5 May 2021 to identify relevant literature. We extracted the prevalence estimates of game addiction from the studies to measure the global prevalence of game addiction. Then, we found the answers to the questions raised and synthesized them into several themes. Results: We identified 2609 articles. Among them, studies that were not related to the topic, duplicated, and that did not meet the selection criteria were excluded, and 18 studies were selected. We rated most of the studies as moderate, and a few were low, and high. A majority of studies found an increase in game usage time and game addiction score during the COVID-19 pandemic. Some children and adolescents in emotional pain play games to communicate with their peers. Regarding parenting, violent parenting and the absence of parental supervision increase levels of game addiction in children. Gaming disorder was caused by the impact of COVID-19 in a vulnerable group with predisposing factors such as depression, anxiety, and attention-deficit/hyperactivity disorder. Adolescents and males scored higher on a game addiction scale, although we could not find any quantitative correlations due to the heterogeneous scales used for gaming addiction. Conclusions: During the COVID-19 pandemic, isolated children and adolescents reported increased gaming hours as a result of coping with their psychological pain and avoiding social isolation. Their parents, who should provide proper supervision, also failed to provide appropriate support due to the stress caused by the pandemic. Mental health providers should educate children, adolescents, and their guardians on alternative ways to relieve stress and help parents effectively control their children's usage of games.